Application of EMG feedback for hand prosthesis control in high-level amputation: a case study - Jack Tchimino; Rehne Lessmann Hansen; Peter Holmberg Jørgensen; Jakob Dideriksen; Strahinja Dosen (Scientific Reports)
Abstract EMG feedback improves force control of a myoelectric hand prosthesis by conveying the magnitude of the myoelectric signal back to the users via tactile stimulation. The present study aimed to test if this method can be used by a participant with a high-level amputation, and whose muscle used for prosthesis control (pectoralis major) was not intuitively related to hand function. Vibrotactile feedback was delivered to the participant’s torso, while the control was tested using EMG from three different muscles. The participant completed four experimental sessions of a force-matching task with a prosthesis. The performance was evaluated by computing the target force success rate. The results of session 1 showed that the participant could effectively employ EMG feedback after only brief training. Session 2 demonstrated that EMG feedback benefited force control, increasing the success rate by approx. 30%. Finally, after proper training (sessions 3 and 4), the participant’s performance when using the muscle on the amputated side was similar to that achieved with the muscles on the contralateral side. Overall, the study results indicate that EMG feedback can be used in high-level amputations, despite the extent of the injury and non-intuitive control.